Physical exercises for the arms and legs to develop speed-strength and its impact on some offensive basketball skills for female students. - Abdullah, Hanaa Abbas; Amin, Nadi Mohammed; Salam, Sarah Hekmat Abdel (Sulaimani Journal for Humanities, 2026)
Basketball is a team sport and a competitive game that showcases strength, speed, and the beauty of its skill performance. This has made it a scientific and methodological subject studied in colleges of physical education and sports sciences, where students are required to perform it optimally during the practical lesson. This requires the presence of physical elements that the students possess, including strength combined with speed, as their availability guarantees achieving what the performance requires, including offensive skills.
Keywords: physical exercises; speed specific strength; offensive skills; basketball